Answer:
The answer is 3) 40.
Step-by-step explanation:
since you're working with the Pythagorean theorem, you should know that a^2+b^2=c^2, therefore, we know that we only have two sides. we have a and c. we know that a = 42 and c = 58, giving us the equation of 42^2+b^2=58^2,
we want to find b!
so we would simply subtract the two.
58^2 - 42^2 = b
b = 1600
now we want to square root,
b = sqrt1600
which in the end, gives us the answer of 40.
Use slip and slide method
p^2-2p-15
(p-5)(p+3)
(p-5/3)(p+3/3)
(p-5/3)(p+1)
(3p-5)(p+1)
Final answer: (3p-5)(p+1)
Answer:
Pretend the y-axis is a mirror
If the original shape is
P=4,-2
Z=5,-4
M=4,-4
The new image made by mirroring it will be
P’= -4,-2
Z’= -5,-4
M’= -4,-4
Step-by-step explanation:
Sorry if this doesn’t make sense, just graph P’, Z’, and M’ for a mirrored image